2013
DOI: 10.1186/1939-8433-6-22
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel prediction method of cis-elements to hypothesize collaborative functions of cis-element pairs in iron-deficient rice

Abstract: BackgroundCis-acting elements are essential genomic sequences that control gene expression. In higher eukaryotes, a series of cis-elements function cooperatively. However, further studies are required to examine the co-regulation of multiple cis-elements on a promoter. The aim of this study was to propose a model of cis-element networks that cooperatively regulate gene expression in rice under iron (Fe) deficiency.ResultsWe developed a novel clustering-free method, microarray-associated motif analyzer (MAMA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…To investigate the cis elements related to changes in spatial gene expression triggered by Fe deficiency and Cd stress, we used MAMA, which is an in silico tool for predicting cis ‐acting elements based on expression ratios by microarray analysis (Kakei et al ., ). MAMA detects cis motifs that occur frequently in a set of promoter sequences of up‐regulated genes, based on sequence similarities and the expression ratio of each up‐regulated gene.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…To investigate the cis elements related to changes in spatial gene expression triggered by Fe deficiency and Cd stress, we used MAMA, which is an in silico tool for predicting cis ‐acting elements based on expression ratios by microarray analysis (Kakei et al ., ). MAMA detects cis motifs that occur frequently in a set of promoter sequences of up‐regulated genes, based on sequence similarities and the expression ratio of each up‐regulated gene.…”
Section: Resultsmentioning
confidence: 97%
“…a). We previously reported that DCEp1 and TATA‐box‐like motifs are important as a unit of the basic transcription machinery to function with other colocalized cis motifs, including stress‐related motifs such as IDEF1‐binding core motif and FAM1 (Kakei et al ., ). The present study suggests that DCEp1 is required for the up‐regulation of Fe deficiency‐inducible genes in all root tissues, while DCEp2 is important in the VB and Cor.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…None of the CaGDPDs possessed PHO (CACGTS) and P responsive (ATGCCAT) elements. Further, we found only one Fe responsive cis-regulatory elements, IDEF1BS (Kakei et al 2013) …”
Section: Multiple P-responsive Cis-acting Elements Are Present In Osgmentioning
confidence: 96%